Social Interaction as a Tool for Teaching Fundamental Pedagogical Aspects to Preschoolers - Iskanderova, Shirin Daniyarovna (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This article explores the significance of social interaction in the teaching and learning process for preschoolers. It discusses how social interaction serves as a crucial tool in cultivating fundamental pedagogical aspects such as communication, collaboration, empathy, and problem-solving skills. By employing various interactive methods, educators can create an enriching learning environment that promotes cognitive and social development in young children. The article also examines practical strategies for incorporating social interaction into preschool curricula and the implications for educational practice.